2018
DOI: 10.1177/0972652718798079
|View full text |Cite
|
Sign up to set email alerts
|

Diversification in Korean Banking Business: Is Non-interest Income a Financial Saviour?

Abstract: This article examines whether the diversification of operating income in Korean banks has persistently enhanced the performance of Korean banks. The results show that, despite Korean banks’ efforts to diversify their operating income, these banks do not gain any benefit from the diversification. Thus, bank managers in Korea focus on interest income revenue. The results also show that the increase in non-interest income revenue keeps pace with the growth in expenses, which offsets the diversification effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
2
5
1
2
Order By: Relevance
“…The position reversed during the transition phase as concentrated operation became most profitable while unrelated diversifiers achieved lower performance (Figure 2b). This is in line with prior research (Varadarajan & Ramanujam, 1987;Wan, 2005;George, 2006;Baek et al, 2018). How can we interpret this reversal in diversification firm performance relationship between the two periods?…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The position reversed during the transition phase as concentrated operation became most profitable while unrelated diversifiers achieved lower performance (Figure 2b). This is in line with prior research (Varadarajan & Ramanujam, 1987;Wan, 2005;George, 2006;Baek et al, 2018). How can we interpret this reversal in diversification firm performance relationship between the two periods?…”
Section: Resultssupporting
confidence: 90%
“…However, research in emerging market contexts has also provided inconsistent results. The study of Singaporean companies showed that with low institutional development and market failures, diversification adds value to shareholders (Chen & Ho, 2000) while other studies showed a negative relationship (Baek, Lee, Lee, & Mohanty, 2018;George 2007). Pawaskar's (1999) Indian study showed that diversification performance relationship depended on the asset utilization of firms.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This findings is in consonance with the works of Alubisia, Githii, and Mwangi (2018), Yang, Li, Ma, and Chen (2018), Adedeji and Adedeji (2018), Huseyin (2018), Mundi (2019), Gueyié, Guidara, and Lai (2019) who examined the effect of noninterest income (disaggregated into noninterest income , fee and commission income, capital adequacy ratio, overheads , foreign exchange income , loans , and bank size) on financial performance and found that commission income had significant positive influence on financial performance of banks while foreign exchange income had negative significant effect on financial performance of banks thus, re-echoing the need for increase and encouragement for the banking sector diversification into noninterest based activities which have proven over the years as an alternative and more efficient revenue generating source for the banks with a view to improving their financial performance and stability. This study however, negates the studies by LiLi (2014), Gichure (2015), Beak, Yong Lee, Wan Lee and Mohanty (2018), and Andrzejuk (2019) who examined the influence of noninterest income on financial performance of banks and found an insignificant influence between commission income, foreign exchange transaction income, firm age, and financial performance of banks.…”
Section: Resultscontrasting
confidence: 81%
“…The relationship is more complicated as it depends on the circumstances and the prevailing state of the economy. It is worth mentioning that most previous studies on non-interest income and bank performance nexus found positive impact (DeYoung & Rice, 2004;Craigwell & Maxwell, 2006;Demirgücç-Kunt & Huizinga, 2010;Karakaya & Er, 2013;Lee et al, 2014;Sun et al, 2017;Al-Tarawneh et al, 2017;Adedeji & Adedeji, 2018;Baek et al, 2018;Al-Slehat & Altameemi, 2021). In contrast, Mndeme (2015) found a negative impact.…”
Section: Introductionmentioning
confidence: 92%
“…On the contrary, Athanasoglou et al (2008) found no significant relationship between bank size and banks performance. Baek et al (2018) affirmed that money incurred by banks in carrying out non-traditional activities is higher than what is incurred on traditional activities, which made the non-interest income to be more volatile. Also, Karakaya & Er (2013); Al-Tarawneh et al (2017) showed a positive linkage between credit creation of DMBs to the size of its profitability despite the extent of banks' exposure to non-performing loans.…”
Section: Introductionmentioning
confidence: 99%